Gender and survival from out-of-hospital cardiac arrest: a New Zealand registry study. Issue 6 (16th April 2018) - Dicker, Bridget; Conaglen, Kate; Howie, Graham
Abstract : Objective: To determine the relationships between survival from all-cause out-of-hospital cardiac arrest (OHCA) and gender in New Zealand. Methods: A retrospective observational study was conducted using data compliant with the Utstein guidelines from the St John New Zealand OHCA Registry for adult patients who were treated for an OHCA between 1 October 2013 and 30 September 2015. Univariate logistic regression was used to investigate factors associated with return of spontaneous circulation sustained to handover at hospital and survival to 30 days. Multivariate logistic regression models were used to investigate outcome differences in survival according to gender at 30 days postevent. Results: Women survived to hospital handover in 29% of cases, which was not significantly different from men (31%). When adjusted for age, location, aetiology, initial rhythm and witnessed status, there was no significant difference in 30-day survival between men (16%) and women (13%) (adjusted OR 1.22, 95% CI (0.96 to 1.55), p=0.11). Conclusion: No statistical differences were found in 30-day survival between genders when adjustments for unfavourable Utstein variables were accounted for.